Next goal wins [videorecording (DVD)] - Waititi, Taika; Waititi, Taika; Morris, Iain, 1973 August 6-; Fassbender, Michael, 1977-; Kightley, Oscar; Kaimana; Fane, David, 1966-; House, Rachel; Koale, Beulah, 1992-; Arnett, Will; Moss, Elisabeth, 1982-; Latukefu, Uli, 1983 or 1984-; et al. (Searchlight Pictures, 2024)
Follows the infamously terrible American Samoa soccer team, known for a brutal 2001 FIFA match they lost 31-0. With the 2014 World Cup Qualifiers approaching, the team hires down-on-his-luck, maverick coach Thomas Rongen, hoping he will turn the world's worst soccer team around in this humorous and heartfelt underdog story.